Organizing Time Banks: Lessons from Matching Markets - Tommy Andersson; Ágnes Csehz; Lars Ehlers; Albin Erlanson (Lund University, School of Economics and Management, Department of Economics, 2019)
A time bank is a group of individuals and/or organizations in a local community that set up a common platform to trade services among themselves. There are several well-known problems associated with this type of banking, e.g., high overhead costs for record keeping and difficulties to identify feasible trades. This paper demonstrates that these problems can be solved by organizing time banks as a centralized matching market and, more specifically, by organizing trades based on a non-manipulable mechanism that selects an individually rational and time-balanced allocation which maximizes exchanges among the members of the time bank (and those allocations are efficient). Such a mechanism does not exist on the general preference domain but on a smaller yet natural domain where agents classify services as unacceptable and acceptable (and for those services agents have specific upper quotas representing their maximum needs). On the general preference domain, it is demonstrated that the proposed mechanism at least can prevent some groups of agents from manipulating the mechanism without dispensing individual rationality, efficiency, or time-balance.
Keywords: D47; D82; 330; market design; time banking; priority mechanism; non-manipulability